Gender, digital financial services and vulnerability in the era of pandemics: A cross-sectional analysis [version 2; peer review: 1 approved, 1 not approved] - Amidu, M.; Akakpo, A.A.; Mensah, J.K.; Asiedu, E. (F1000 Research, 2023)
Background: The COVID-19 pandemic has rapidly spread across the world, infecting millions, and causing economic disruption on an unprecedented scale. While everyone is affected by the COVID-19 pandemic, vulnerable communities are at the greatest risk. This study aims to examine the relationship between digital financial services (DFS), gender, and the vulnerability of informal settlement dwellers to COVID-19. Methods: We sampled a total of 2,697 households from 101 informal settlements across eleven out of sixteen administrative regions of Ghana. The regions were selected based on the relative severity of the pandemic, and the associated national lockdown regulations. Results: Adopting the ordinary least square analytical technique, the results reveal three main findings: First, we observe that males in informal settlements are more exposed to infected people or a person who died from COVID-19 than females. However, women are more vulnerable to the pandemic than men as vulnerable populations have a higher susceptibility to pandemics due to less capacity to implement preparedness and response strategies due to disparities in their societal status. Finally, we find that the vulnerability of informal dwellers is moderated using digital financial services. Conclusions: We conclude that there exist gender disparities regarding COVID-19 exposure and vulnerability. Also, by making use of digital financial services vulnerable groups can reduce their exposure to the COVID-19 pandemic. Our results provide policy implications for authorities designing policies to educate men more on the need to take preventive measures seriously as well as educate vulnerable populations to adopt digital financial services.
Research Article
Keywords: Digital financial services; Gender; Vulnerability